Discrimination of positional isomers by ion mobility mass spectrometry: application to organic semiconductors. Issue 20 (15th May 2018) - Duez, Quentin; Romain, Maxime; Tonneaux, Corentin; De Winter, Julien; Lemaur, Vincent; Cornil, Jérôme; Poriel, Cyril; Gerbaux, Pascal
Abstract : Ion mobility mass spectrometry is introduced as a versatile technique for positional isomerism discrimination in the field of organic-based optoelectronics. Abstract : Organic semiconductors are increasingly being used in organic-based opto-electronic devices. Since regioselective synthetic approaches are not always controlled, promising compounds are sometimes prepared following non-regioselective routes. Ion mobility mass spectrometry is here introduced as a direct method to distinguish isomers in mixtures, instead of undertaking time-consuming analytical chromatography procedures.